INFLAMMATION AND SALT IN YOUNG ADULTS: THE AFRICAN-PREDICT STUDY. (April 2021) - Crouch, Simone; Roux, Shani Botha-Le; Delles, Christian; Graham, Lesley A.; Schutte, Aletta E.
Abstract : Objective: Low-grade inflammation and a diet high in salt (sodium) are both established risk factors for cardiovascular disease. High potassium intake attenuates increases in blood pressure in response to high salt intake and may have a similar protective effect on the modulation of inflammation. To better understand these interactions under normal physiological conditions, we investigated the relationships between 22 inflammatory mediators with 24hr urinary potassium in young healthy adults stratified by low, middle and high salt intake (sodium tertiles). We additionally stratified by ethnicity due to salt-sensitivity seen in black populations. Design and method: We included 991 healthy black (N = 457) and white (N = 534) adults, aged 20–30 years with complete data for 24hr urinary sodium and potassium. Blood samples were analysed for 22 inflammatory mediators. Results: Differences between plasma concentrations of inflammatory mediators between the low, middle and high sodium tertiles were not seen in either the black or white groups. In multivariable-adjusted regression analyses in white adults, we found only in the lowest sodium tertile that potassium associated negatively with the pro-inflammatory mediators interferon gamma, interleukin-7, interleukin -12, interleukin -17A, interleukin -23 and tumor necrosis factor alpha (all p greater than or equal to 0.046). In the black population, we found no independent associations between potassium and any inflammatory mediator were found. Conclusions: In young white adults 24 h potassium associated independently and negatively with specific pro-inflammatory mediators, but only in those with a daily salt intake less than 6.31 grams, suggesting potassium to play a protective, anti-inflammatory role in a low-sodium environment. No similar associations were found in young healthy black adults.